Sequence Divergence of the Enniatin Synthase Gene in Relation to Production of Beauvericin and Enniatins in Fusarium Species - Agnieszka Waśkiewicz; Łukasz Stępień (Toxins, 2013)
Beauvericin (BEA) and enniatins (ENNs) are cyclic peptide mycotoxins produced by a wide range of fungal species, including pathogenic Fusaria. Amounts of BEA and ENNs were quantified in individual rice cultures of 58 Fusarium strains belonging to 20 species, originating from different host plant species and different geographical localities. The species identification of all strains was done on the basis of the tef-1α gene sequence. The main aim of this study was to analyze the variability of the esyn1 gene encoding the enniatin synthase, the essential enzyme of this metabolic pathway, among the BEA- and ENNs-producing genotypes. The phylogenetic analysis based on the partial sequence of the esyn1 gene clearly discriminates species producing exclusively BEA from those synthesizing mainly enniatin analogues.